Impact of preoperative biliary drainage on 30 Day outcomes of patients undergoing pancreaticoduodenectomy for malignancy. Issue 4 (April 2022) - Werba, Gregor; Napolitano, Michael A.; Sparks, Andrew D.; Lin, Paul P.; Johnson, Lynt B.; Vaziri, Khashayar
Abstract: Background: Preoperative biliary drainage (PBD) has been advocated to address the plethora of physiologic derangements associated with cholestasis. However, available literature reports mixed outcomes and is based on largely outdated and/or single-institution studies. Methods: Patients undergoing PBD prior to pancreaticoduodenectomy (PD) for periampullary malignancy between 2014-2018 were identified in the ACS-NSQIP pancreatectomy dataset. Patients with PBD were propensity-score-matched to those without PBD and 30-day outcomes compared. Results: 8, 970 patients met our inclusion criteria. 4, 473 with obstruction and PBD were matched to 829 with no preoperative drainage procedure. In the non-jaundiced cohort, 711 stented patients were matched to 2, 957 without prior intervention. PBD did not influence 30-day mortality (2.2% versus 2.4%) or major morbidity (19.8% versus 20%) in patients with obstructive jaundice. Superficial surgical site infections (SSIs) were more common with PBD (6.8% versus 9.2%), however, no differences in deep or organ-space SSIs were found. Patients without obstruction prior to PBD exhibited a 3-fold increase in wound dehiscence (0.5% versus 1.5%) additionally to increased superficial SSIs. Conclusion: PBD was not associated with an increase in 30-day mortality or major morbidity but increased superficial SSIs. PBD should be limited to symptomatic, profoundly jaundiced patients or those with a delay prior to PD.